FRUIT PRODUCTION OF A SIX-YEAR OLD SHOREA STENOPTERA PLANTATION AT HAURBENTES, BOGOR, INDONESIA - EIZI SUZUKI (SEAMEO BIOTROP, 1989)
A six-year old plantation of Shorea stenoptera at Haurbentes, Bogor flowered for the first time on October, 1987. In plots of 270 m2, 12 of the 32 trees had opened flowers. The average heights of flowering and non-flowering trees were 400 cm and 270 cm, respectively. The flowers and fruits were counted four times from October 28, 1987 until February 17, 1988. In October, a total of 24313 flowers existed and 1.9% of them became mature fruits on February, 1988. The fruit production was 308 kg/ha and 133 kg/ha in fresh and dry weights, respectively.